Cryptology Transmitted Message Protection : From Deterministic Chaos up to Optical Vortices /: From Deterministic Chaos up to Optical Vortices. (2016) - Izmailov, Igor; Poizner, Boris; Romanov, Ilia; Smolskiy, Sergey
No abstract available